Benchmarking between regional innovation systems: the case of Santander and Antioquia, Colombia (2016)
This article analyzes the performance of two important states of Colombia in terms of Science, Technology and Innovation, STI. To achieve this, a descriptive-analytical methodology is used and a comparative analysis, or benchmarking, is implemented between the Regional Innovation System, RIS, from Santander and the RIS from Antioquia. This work aims not only to contribute to the creation of a current perspective of the RIS studied, but also to guide through the strengths and weaknesses to a creation and design of policies or programs that encourage the processes of generation and dissemination of knowledge in the state of Santander. The results show that Santander presents a significant lag in terms of STI with respect to Antioquia. This is a reflection of the limited participation of the productive sector in the strengthening of innovation capabilities, unequal participation of stakeholders in initiatives of STI, and low levels of Activities of Investment in Science, Technology, and Innovation. It is recommended that Santander works on some important aspects to achieve better results in the processes of innovation in all the state.